Integrin signaling in cancer: bidirectional mechanisms and therapeutic opportunities - Siyi Li; Chibuzo Sampson; Changhao Liu; Hai-long Piao; Hong-Xu Liu (Cell Communication and Signaling, 2023)
Abstract Integrins are transmembrane receptors that possess distinct ligand-binding specificities in the extracellular domain and signaling properties in the cytoplasmic domain. While most integrins have a short cytoplasmic tail, integrin β4 has a long cytoplasmic tail that can indirectly interact with the actin cytoskeleton. Additionally, 'inside-out' signals can induce integrins to adopt a high-affinity extended conformation for their appropriate ligands. These properties enable integrins to transmit bidirectional cellular signals, making it a critical regulator of various biological processes. Integrin expression and function are tightly linked to various aspects of tumor progression, including initiation, angiogenesis, cell motility, invasion, and metastasis. Certain integrins have been shown to drive tumorigenesis or amplify oncogenic signals by interacting with corresponding receptors, while others have marginal or even suppressive effects. Additionally, different α/β subtypes of integrins can exhibit opposite effects. Integrin-mediated signaling pathways including Ras- and Rho-GTPase, TGFβ, Hippo, Wnt, Notch, and sonic hedgehog (Shh) are involved in various stages of tumorigenesis. Therefore, understanding the complex regulatory mechanisms and molecular specificities of integrins are crucial to delaying cancer progression and suppressing tumorigenesis. Furthermore, the development of integrin-based therapeutics for cancer are of great importance. This review provides an overview of integrin-dependent bidirectional signaling mechanisms in cancer that can either support or oppose tumorigenesis by interacting with various signaling pathways. Finally, we focus on the future opportunities for emergent therapeutics based on integrin agonists. Video Abstract